Pengaruh Kualitas Layanan dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Pada Cafe Sintesis Coffee Di Kabupaten Karawang - Siska Dwi Rahayu; Danang Kusnanto (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study is to knowing, analyzing, and explaining the phenomenon of the effect of service quality and Electronic Word of Mouth on purchasing decisions at the Synthesis coffee cafe in Karawang Regency. This study uses quantitative methods with descriptive and verification analysis. Sampling in this study used incidental sampling with a sample of 262 respondents, namely visitors to the Synthesis Coffee cafe in Karawang Regency. The data analysis tools used are path analysis techniques and scale range analysis with the help of the Method of Succesive Interval (MSI) and using SPSS version 22. The results show that Service Quality and Electronic Word of Mouth have a strong relationship, as well as Service Quality and Electronic Word of Mouth has a positive and significant effect on Purchase Decisions.